De-Ubiquitinating Enzymes USP21 Regulate MAPK1 Expression by Binding to Transcription Factor GATA3 to Regulate Tumor Growth and Cell Stemness of Gastric Cancer - Guo, Qingqu; Shi, Dike; Lin, Lele; Li, Hongbo; Wei, Yunhai; Li, Baozhong; Wu, Dan (Frontiers in Cell and Developmental Biology, 2021)
USP21 is a kind of deubiquitinating enzymes involved in the malignant progression of various cancers, while its role in gastric cancer (GC) and the specific molecular mechanism are still unclear. This study probed into the function of USP21 in vitro and in vivo, and discussed the regulatory mechanism of USP21 in GC in vitro. We reported that USP21 promoted GC cell proliferation, migration, invasion, and stemness in vitro, and regulated GC tumor growth and cell stemness in mice in vivo. USP21 stabilized the expression of GATA3 by binding to GATA3. Besides, GATA3 also regulated the expression of MAPK1 at the transcriptional level. A series of in vitro experiments testified that USP21 regulated the expression of MAPK1 by binding to transcription factor GATA3, thereby regulating the tumor growth and cell stemness of GC. Overall, this study identified a new USP21/GATA3/MAPK1 axis, which plays a pivotal role in promoting the malignant progression of GC and might provide a potential target for treatment.